SÜLEYMAN I: MOMEN KEJAYAAN DAN AWAL KERUNTUHAN OTTOMAN - Al-Hakim, Dzaky Nabil; Annur, Fauzi (Institut Agama Islam Ngawi, 2025)
This study explores the leadership of Sultan Suleiman I (1520-1566), focusing on the reforms he implemented and their impact on the stability and prosperity of the Ottoman Empire, as well as the ambiguities in the line of succession that contributed to the empire's decline. The aim of the research is to analyze reforms in the fields of economy, military, culture, and politics, along with the implications of internal conflicts among Suleiman's sons. The methodology employed is historical research consisting of five stages: topic selection, source collection, verification, interpretation, and historiography, utilizing data from books, journals, and articles. This research differs from previous studies that primarily emphasize the positive aspects of Suleiman's leadership by highlighting the failures in succession training and the resulting internal tensions. The findings indicate that while Suleiman I achieved significant advancements, his lack of attention to succession training and clear lines of succession contributed to the decline of power and influence of the Ottoman Empire after his death, underscoring the importance of effective leadership in maintaining the continuity of a kingdom. Keywords: Sultan Suleiman I, Ottoman Empire, Leadership, Decline.